The Roots of Ethnic Conflict in Africa
XII, 208 p.
Keywords: This book focuses on the problem of ethnic conflict in Africa and seeks to explain its root causes. The main thesis of the book is that ethnic political mobilization is essentially a function of deeply-felt grievances on the part of the groups so mobilized.